EMOTIONAL INTELLIGENCE IN THE STRUCTURE OF ADAPTATION PROCESS OF FUTURE HEALTHCARE PROFESSIONALS - Halian, Andriy; Halian, Ihor; Burlakova, Iryna; Shevchenko, Rosina; Lappo, Violetta; Zhigarenko, Igor; Popovych, Ihor (Revista Inclusiones, 2020)
The study presents the empirical research on emotional intelligence as a factor of efficient adaptation of future healthcare professionals to their professional environment. It considers emotional intelligence as a complex construct of mental abilities related to handling emotional information and generating emotional experience of an individual. Cluster analysis is used to determine the levels of adaptiveness: high (16.59%), medium (38.57%) and low (44.84%). The study determines the indexes of intercorrelation of the components of social and psychological adaptation of the future healthcare professionals; it diagnoses the level of manifesting emotional intelligence in the future healthcare professionals with different levels of adaptiveness (р≤.05; р≤.01). The research focuses on the differences in the structure of emotional intelligence of well-adapted and badly-adapted future healthcare professionals (р≤.05; р≤.01) to their professional environment. The structure is represented by the content characteristics: understanding of one’s own emotions and other people’s emotions, managing one’s own emotions and other people’s emotions; emotional competence; emotional experience. The study proves that empathy, emotional competence and self-improvement are the factors ensuring an appropriate level of adaptation of future healthcare professionals to their professional environment.